Enhanced acetylene semi-hydrogenation on a subsurface carbon tailored Ni–Ga intermetallic catalyst. Issue 37 (9th June 2022) - Ge, Xiaohu; Ren, Zhouhong; Cao, Yueqiang; Liu, Xi; Zhang, Jing; Qian, Gang; Gong, Xueqing; Chen, Liwei; Zhou, Xinggui; Yuan, Weikang; Duan, Xuezhi
Abstract : A subsurface carbon tailored Ni–Ga intermetallic catalyst delivers superior catalytic performance for acetylene semi-hydrogenation. Abstract : Tailoring the active sites to promote the formation of the target product is of great importance for selective hydrogenations catalyzed by non-noble metals but remains challenging. Herein, we propose to employ carbon atoms to be incorporated into the Ni3 Ga intermetallic with partially isolated Ni sites aiming to enhance the catalytic performances for acetylene semi-hydrogenation. The incorporation of carbon atoms into the lattice of the Ni3 Ga intermetallic is achieved by thermal processing of the Ni3 Ga intermetallic catalyst in an acetylene atmosphere. The processed catalyst is proven to show the typical Ni3 GaC0.5 phase by multiple characterization techniques including atomic-resolution electron microscopy and X-ray absorption spectroscopy. The presence of subsurface carbon in the Ni3 GaC0.5 catalyst is experimentally and theoretically demonstrated to synergize with Ga sites for modifying the electronic structures of Ni via obvious hybridization of Ni 3d with Ga 2p and C 2p orbitals. The performance tests show that the Ni3 GaC0.5 catalyst delivers high ethylene selectivity, up to ca. 90% at full conversion of acetylene, which outperforms the referred Ni and Ni3 Ga catalysts. The excellent selectivity to ethylene is rationalized by theoretical calculations, which point out that the desorption of ethylene from the Ni3 GaC0.5 catalyst is kinetically more favourable than its hydrogenation to ethane. In addition, the stability of the Ni3 GaC0.5 catalyst is also enhanced against the Ni and Ni3 Ga catalysts due to the suppressed formation of C4 products.